2010
DOI: 10.1097/dad.0b013e3181cd4396
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Changes and the Expression of Alpha-Melanocyte Stimulating Hormone and Melanocortin-1 Receptor in Melasma Lesions: A Comparative Study

Abstract: Melasma is a common acquired symmetrical hypermelanosis characterized by irregular light- to dark-brown macules on sun-exposed skin areas. The literature shows few studies on its physiopathogeny. However, changes in α-melanocyte stimulating hormone (α-MSH) secretion and melanocortin-1 receptor (MC1-R) expression may play a role to trigger this condition. Biopsies were taken from both melasma skin and adjacent perilesional normal skin of 44 patients. The biopsies were submitted for hematoxylin and eosin and Fon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 47 publications
5
39
0
Order By: Relevance
“…Fontana-Masson staining has shown that, the melanin content of melasma skin is higher in all layers of the epidermis, including the stratum corneum, than that in perilesional normal skin [7][8][9]. Image analysis of Fontana-Massonstained sections of skin from 22 patients with melasma showed a significant difference in the density of melanin between melasma skin (mean ± standard deviation [SD]: 0.37 ± 0.02) and perilesional normal skin (0.34 ± 0.02) (p<0.01) [10]. These findings indicate that the development of melasma involves accelerated melanin synthesis, increased levels of melanin transfer to the keratinocytes, and reduced melanin degradation.…”
Section: Epidermal Hyperpigmentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Fontana-Masson staining has shown that, the melanin content of melasma skin is higher in all layers of the epidermis, including the stratum corneum, than that in perilesional normal skin [7][8][9]. Image analysis of Fontana-Massonstained sections of skin from 22 patients with melasma showed a significant difference in the density of melanin between melasma skin (mean ± standard deviation [SD]: 0.37 ± 0.02) and perilesional normal skin (0.34 ± 0.02) (p<0.01) [10]. These findings indicate that the development of melasma involves accelerated melanin synthesis, increased levels of melanin transfer to the keratinocytes, and reduced melanin degradation.…”
Section: Epidermal Hyperpigmentationmentioning
confidence: 99%
“…In contrast, a study by Grimes et al [11] of 22 skin specimens from subjects with Fitzpatrick skin types IV-VI immunostained using Mel-5, did not find a significant increase in melanocyte numbers in melasma skin compared with perilesional normal skin. Moreover, in their study of 44 patients with melasma, Miot et al [10] did not find any differences in melanocyte numbers between melasma skin and perilesional normal skin sections labeled using a Melan-A antibody.…”
Section: Epidermal Hyperpigmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…[59][60][61] Melanocytes in the melasma lesion are larger and have more developed dendrites compared to those in the normal tissues. [59][60][61] The basement membrane is also damaged, presenting pendulous melanocytes that protrude into the dermis.…”
Section: Fractional Lasersmentioning
confidence: 99%
“…[59][60][61] Melanocytes in the melasma lesion are larger and have more developed dendrites compared to those in the normal tissues. [59][60][61] The basement membrane is also damaged, presenting pendulous melanocytes that protrude into the dermis. 62,63 Along with these findings, other noticeable histochemical characteristics include increased inflammatory cytokines, elevated levels of melanogenesis-associated proteins, and signs suggesting UV-induced skin damage.…”
Section: Fractional Lasersmentioning
confidence: 99%